1992
DOI: 10.1111/j.1467-6494.1992.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic, Extrinsic, and Amotivational Styles as Predictors of Behavior: A Prospective Study

Abstract: This research ascertained the role of intrinsic, extrinsic, and amotivational styles as predictors of behavioral persistence in a real-life setting. At the beginning of the academic year, 1,042 first-tertn junior-college students enrolled in a compulsory college course completed a scale assessing intrinsic motivation, four styles of extrinsic motivation (namely, external regulation, introjection, identification, and integration), and amotivation toward academic activities. At the end of the semester, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
545
8
73

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(666 citation statements)
references
References 53 publications
40
545
8
73
Order By: Relevance
“…Specifically, we objectively assessed 7 days of energy expenditure in freeliving conditions to obtain assessments of the participants' behavioral persistence, intensity, and frequency of exercise behavior. This approach is similar to past work that has employed behavioral persistence as a field-based alternative to assessing Motivation and Bouts of Exercise 339 free-choice behavior (e.g., Pelletier et al, 2001;Vallerand & Bissonnette, 1992), and permits the testing of the utility of autonomous versus controlled motivation in predicting purposeful exercise behavior.With regard to the behavioral concomitants of motivation in the exercise domain, Ryan and Deci (2007) assert that sustained exercise behavior is most likely when an individual partakes in the activity for autonomous reasons (i.e., they act through intrinsic motivation and well-internalized extrinsic motivation). Recent research has corroborated such theoretical reasoning by supporting the adaptive benefits of autonomous motivation.…”
mentioning
confidence: 81%
“…Specifically, we objectively assessed 7 days of energy expenditure in freeliving conditions to obtain assessments of the participants' behavioral persistence, intensity, and frequency of exercise behavior. This approach is similar to past work that has employed behavioral persistence as a field-based alternative to assessing Motivation and Bouts of Exercise 339 free-choice behavior (e.g., Pelletier et al, 2001;Vallerand & Bissonnette, 1992), and permits the testing of the utility of autonomous versus controlled motivation in predicting purposeful exercise behavior.With regard to the behavioral concomitants of motivation in the exercise domain, Ryan and Deci (2007) assert that sustained exercise behavior is most likely when an individual partakes in the activity for autonomous reasons (i.e., they act through intrinsic motivation and well-internalized extrinsic motivation). Recent research has corroborated such theoretical reasoning by supporting the adaptive benefits of autonomous motivation.…”
mentioning
confidence: 81%
“…Black and Deci (2000) found that undergraduate students who took a chemistry class for less autonomous reasons were more likely to drop out of the course. Autonomous regulation has also been associated with persistence in junior-college students (Vallerand & Bissonnette, 1992) and high school students (Vallerand, Fortier & Guay, 1997), whereas controlled regulation was negatively associated with persistence.…”
mentioning
confidence: 99%
“…w organizacji jest uważana za czynnik ułatwiający dostęp do informacji i innych zasobów w organizacji [Fukuyama, 1995;Ibarra, 1997;Moss Kanter, 1993;Timberlake, 2005]. Wielu naukowców bada relacje między motywacją i pożądany-mi (pozytywnymi) zachowaniami pracowniczymi, takimi jak: kreatywność [Amabile, 1993], elastyczność poznawcza [Gagne, Deci, 2005], uczenie się [Vallerand, Bissonnette, 1992;Vansteenkiste et al, 2004, Bolino, 1999Gagne, 2003;Weisten, Ryan, 2010], dzielenie się wiedzą [Foss, Minbaeva, Pedersen, Reinhold, 2009;Gagne, 2009;Lin, 2007].…”
Section: Pozytywne Podejście W Naukach O Zarządzaniuunclassified